Solanum paniculatum L. decreases levels of inflammatory cytokines by reducing NFKB, TBET and GATA3 gene expression in vitro. (14th September 2017) - Rios, Raimon; Silva, Hugo Bernardino Ferreira da; Carneiro, Norma Vilany Queiroz; Pires, Anaque de Oliveira; Carneiro, Tamires Cana Brasil; Costa, Ryan dos Santos; Marques, Cintia Rodrigues; Machado, Marta Santos Serafim; Velozo, Eudes da Silva; Silva, Telma M.G. da; Silva, Tania M.S. da; Conceição, Adilva de Souza; et al.
Abstract: Ethnopharmacological relevance: Solanum paniculatum L., popularly known as jurubeba, is a common subtropical plant from Brazil, Paraguay, Bolivia and Argentina, that is used in folk medicine for the treatment of anemia, gastrointestinal disorders and inflammatory conditions in general. In addition to that, an ethnobotanical survey in "Todos os Santos" Bay have pointed out S. paniculatum as an herb to treat asthma. Previous publications have shown that S. paniculatum possesses antibiotic, antioxidant and modulatory effects on gastric acid secretion; however, its anti-inflammatory potential remains unexplored. Aim of the study: Herein, we analyzed the S. paniculatum fruits hexane extract ( Sp E) for the presence of stigmasterol and β-sitosterol and investigated the anti-inflammatory effect of Sp E in vitro. Materials and methods: Sp E was subjected to high-performance liquid chromatography (HPLC) for standardization and quantification of stigmasterol and β-sitosterol. Spleen cells from BALB/c mice were cultivated and stimulated with pokeweed mitogen and also exposed to 15, 30 and 60 µg/mL of Sp E. Following treatment, levels of IFN-γ, IL-4 and IL-10 in the culture supernatants were assessed by ELISA. We also evaluated nitric oxide (NO) production by murine LPS-stimulated peritoneal macrophages using the Griess technique. In addition, the ability of Sp E to stabilize membranes was assessed using a model of hemolysis induced by heat on murine erythrocytes. Gene expression of Th1-cell-specific Tbx21 transcription factor ( TBET ), zinc-finger transcription factor-3 ( GATA3 ), and nuclear factor-κB ( NFKB ) in murine spleen cells were assessed by quantitative Polymerase Chain Reaction (qRT-PCR). Results: Sp E at 15, 30 and 60 µg/mL significantly attenuated cell proliferation, decreased IL-4 release, reduced NO production and improved erythrocyte membrane stabilization in a concentration-dependent manner. Sp E was also able to decrease the release of IFN-γ without altering IL-10 levels. The mechanism whereby Sp E decreased inflammatory markers may be related to the reduction of NFKB, TBET and GATA3 gene expression. Conclusions: This study is the first to test the anti-inflammatory action of S. paniculatum . Herein, we provided evidence for the popular use of S. paniculatum in inflammatory conditions. Additional studies must be conducted to further explore the anti-inflammatory potential of Sp E and to elucidate possible clinical applications. Graphical abstract: